Physical seed dormancy in Abrus precatorious (Ratti): a scientific validation of indigenous technique. (4th February 2021) - Bajwa, Ali; Sharma, Rajender Kumar
Abstract: Seeds of Abrus precatorius L. (Fabaceae) were used as weight measure by Indigenous people. Where, the seeds were referred as Ratti; a traditional Indian unit of mass measurement. Seed weight fluctuates depending upon age, moisture, storage-period/conditions. Therefore, use of seeds as a weighing unit become dubious and need to be validated. For this purpose, seeds of A. precatorious were subjected to different moisture conditions and periodically monitored. Surprisingly, there was no change in seed weight was observed, indicating the impermeability of seed coat. The later was confirmed by scarification of seed coat which resulted in 53% increase in seed weight against 0% in control. Further, presence of a potent toxin (abrin) in the seed coat protects it from pests and microbes, and contributes to the maintenance of impermeability for longer period of time. The data validates the use of A. precatorious seeds as a weighing unit (ratti) by the indigenous people and discussed.